The Intersection of Self-Actualization, Entrepreneurship and Transformational Leadership: A Review of Maslow’s Perspective of Eupsychian Management - Akilu, Nura S.; Junaidu, Abubakar Sambo (American Journal of Trade and Policy, 2015)
An entrepreneur is someone often associated with venture creation, through what could be termed as bold undertaking; a process of treading an unfamiliar terrain characterized by overwhelming challenges known as entrepreneurship. Similarly the self actualizing individual is perceptive of possibilities and engaged in pursuits of interest that could otherwise be deemed unattainable by the multitude. These two, share commonalities akin to commitment to a purpose, meaningful enough to be sustainable and yet do not operate in isolation. They both work to inspire, motivate and organize people of shared vision in the direction of their dreams through transformational leadership. Interestingly too, there seem to be a point of convergence that characterize the seemingly varied motives, leadership style, and what could be seen as distinct set of attributions in the definitions of an entrepreneur and the self-actualizing individual. This possibility stems from the assumption that the quest for entrepreneurial success is more or less associated with the need for self actualization and forms the phenomena of interest this paper aims to explore with a view to establishing a meaningful convergence. Drawing from qualitative analysis of related literature and Abraham Maslow’s works in particular, effort has been made towards this end. The findings revealed a synchronized form of the phenomena with implications that resonate around Maslow’s Idea of Eupsychian Management with a recommendation for practical adoption of the concept.